De fora pra dentro: a dança contemporânea em Uberlândia (1980 2001) - Costa, Panmela Tadeu (2014)
This research aims to analyze the initial scenario of contemporary dance in Uberlandia city between the decades of 1980, 1990 and the early 2000s. This, by itself, restricts the other goal aimed in this research that is the conceptual discussion on the question: what is contemporary dance? Thus, what is to be understood is how the historical relations, represented by the active artists in Uberlandia during the period established, cooperate in constructing a concept of contemporary dance. Hence, the methodology of oral history was chosen in order to understand the established historical context by means of the speeches of the interviewed artists. The theoretical questions about the subject and the bibliography about the ‗contemporary question emerged as a support for the construction on an identitary thought of dance. Among the methods used to reach the aimed goals are two ways of getting in touch with historical sources: consulting the diary editions published between 1990-1999 of the Jornal Correio de Uberlândia, at the Municipal Public Archive, and interviewing artists who were able to offer information about the settled historical context. In short, looking at what had been done and the goals reached, the inquiry aspires to create a solid research source for dance artists, to reaffirm a artistic-cultural identity for the city, to contribute to the development of the academic area related with dance which is relatively new in the local university circles , and to contribute to discussions on contemporary dance in general, as the debate involving its concept is quite difficult.